1999
DOI: 10.1046/j.1365-4362.1999.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

Maggot therapy for the treatment of intractable wounds

Abstract: Maggot therapy is a relatively rapid and effective treatment, particularly in large necrotic wounds requiring debridement and resistant to conventional treatment and conservative surgical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 15 publications
3
86
0
4
Order By: Relevance
“…[17][18][19]21,22 ) and experience with the technique (Box 1). 25 Patients were recorded as overweight accordingly.…”
Section: Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19]21,22 ) and experience with the technique (Box 1). 25 Patients were recorded as overweight accordingly.…”
Section: Outcomementioning
confidence: 99%
“…21 Success rates of MDT, reported in the literature, vary, but seem to be around 80-90%. 18,19,22 The present study discusses the observations of MDT in patients with complex and chronic wounds in whom major limb amputation or sepsis was the only alternative, if no MDT would be performed. In total, 101 patients with 117 wounds, seen in our surgical department, were treated.…”
mentioning
confidence: 99%
“…By 1934, more than 1,000 surgeons were using maggot therapy, the surgical maggot were available commercially from Lederle Corporation (18). MDT is indicated for open wounds and ulcers that contain gangrenous or necrotic tissues with or without infection (19). It was reported that larvae and their secretions have antibacterial effects, reduce inflammation as well as neo-angiogenesis, and improve wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…4) While its therapeutic effects vary among reports, MDT has been effective in about 80%-90% of patients. [5][6][7] MDT has also been reported to be effective for the treatment of pressure ulcer, 8) burn injury, 9) osteomyelitis, 10) diabetic ulcer, 11) ulcers associated with venous stasis, 12) MRSA infection, 13) and chronic intractable ulcers. 14) Age has been suggested as a factor that affects the therapeutic effect of MDT, 15) but these factors have not been evaluated in detail.…”
Section: Disclosure Statementmentioning
confidence: 99%